Conditional Cash Transfers in Education : Design Features, Peer and Sibling Effects Evidence from a Randomized Experiment in Colombia - Barrera-Osorio, Felipe; Bertrand, Marianne; Linden, Leigh L.; Perez-Calle, Francisco (World Bank, Washington, DC, 2012)
This paper presents an evaluation of multiple variants of a commonly used intervention to boost education in developing countries - the conditional cash transfer - with a student level randomization that allows the authors to generate intra-family and peer-network variation. The analysis tests three treatments: a basic conditional cash transfer treatment based on school attendance, a savings treatment that postpones a bulk of the cash transfer due to good attendance to just before children have to re-enroll, and a tertiary treatment where some of the transfers are conditional on students' graduation and tertiary enrollment rather than attendance. On average, the combined incentives increase attendance, pass rates, enrollment, graduation rates, and matriculation to tertiary institutions. Changing the timing of the payments does not change attendance rates relative to the basic treatment but does significantly increase enrollment rates at both the secondary and tertiary levels. Incentives for graduation and matriculation are particularly effective, increasing attendance and enrollment at secondary and tertiary levels more than the basic treatment. There is some evidence that the subsidies can cause a reallocation of responsibilities within the household. Siblings (particularly sisters) of treated students work more and attend school less than students in families that received no treatment. In addition, indirect peer influences are relatively strong in attendance decisions with the average magnitude similar to that of the direct effect.